A Multifaceted Approach to the Mental Health Advantage of the Married: Assessing How Explanations Vary by Outcome Measure and Unmarried Group - Bierman, Alex; Fazio, Elena M.; Milkie, Melissa A. (Journal of family issues, 2006)
This study takes a multifaceted approach to examining reasons for the well-noted mental health advantage of the married. The authors examine whether socioeconomic resources and psychosocial resources explain this advantage for three aspects of mental health by comparing the consistently married to different types of unmarried individuals, as well as the remarried. The authors find that even though the consistently married generally fare better than all the other groups, the reasons for this advantage not only varied by category of marital status but also, for any specific group, these reasons are sometimes varied depending on the aspect of mental health being examined. This study demonstrates that not only is it advisable for researchers to use a variety of outcome measures to understand the mental health advantage of the married, they should also consider how different resources may explain this advantage, depending on the outcomes and groups being examined.